Interaction of Heparin with Fibrinolysis - Holemans, Rudolf; Adamis, Dionysios; Horace, James F (Thrombosis and Haemostasis, 1963)
Heparin in high concentration inhibits the fibrinolysis of human plasma clots or bovine fibrin by fibrinolytic agents which produce plasminogen activation. Heparin has no effect on the fibrinolytic activity of plasmin or Aspergillus protease.In order to produce inhibition of plasminogen activation heparin requires the presence of a co-factor which is present in citrated human plasma but absent from its euglobulin fraction.In none of the concentrations tested has heparin an enhancing effect on fibrinolysis.